Parental Influence on Talent Identification for Players in Rugby Clubs in Kenya - Otieno, Michael D.; Nteere, Jacob; Onywera, Vincent; Akala, Winston (American Journal of Social Sciences and Humanities, 2020)
The role of parents in socialization into sports of athletes has been a topical issue among sociologists and sport scientists from the west for decades. Thus the purpose of the study was to investigate the influence of parents on talent identification for players in rugby clubs in Kenya. The study was guided by the hypothesis that “there is no significant difference in the mean rugby talent identification index when the parental influence of the rugby players is classified as high or low” The factors that were investigated included the parents’ socio-economic status and the parents’ level of education. Data were collected using Questionnaires and interviews from rugby players (n= 125) and coaches (n=15) during the 2017/2018 Kenya Rugby Union league competition. Data were analysed through both descriptive and inferential statistics of Chi- square test of independent measures. Results showed that parental influence on talent identification in Kenya is not significant despite the majority (53.77%) of the coaches indicating that the socio-economic status and the level of education of the parents had an influence on talent identification. Subsequently, future studies need to be conducted to unearth the role of the entire family environment at all stages of the players’ athletic development due to the complexity of the family phenomenon.